Blade‐Cast Nonfullerene Organic Solar Cells in Air with Excellent Morphology, Efficiency, and Stability. Issue 22 (17th April 2018) - Zhang, Lin; Lin, Baojun; Hu, Bo; Xu, Xianbin; Ma, Wei
Abstract: Blade‐coating serving as a prototype tool for slot‐die coating can be very compatible with large‐area roll‐to‐roll coating. Using blade‐coating in an ambient environment, an average power conversion efficiency (PCE) of 10.03% is achieved in nonfullerene organic solar cells, which is higher than that of the optimal spin‐coated device with a PCE of 9.41%. It is demonstrated that blade‐coating can induce a higher degree of molecular packing for both conjugated polymer donors and small‐molecular acceptors as it helps to produce a seeding film containing numerous crystal grains, subsequently providing nucleation sites for the residual solution when the motion of the blade exposes a liquid front. Due to this effect, blade‐coating can partially replace the role of the additive 1, 8‐diiodooctane (DIO) and thus achieves the optimized morphology with fewer additives. Moreover, it is found that the blade‐coated film with 0.25% DIO possesses not only a smaller domain size but also higher domain purity, suggesting more D/A (donor/acceptor) interfaces and a purer phase domain as compared to the spin‐coated film with 1% DIO. Encouragingly, the blade‐coated device with less DIO (0.25%) exhibits much better stability than the spin‐coated device with 1% DIO, showing excellent prospects. Abstract : A blade‐coated device with a lower amount of 1, 8‐diiodooctane (DIO) (0.25%) based on PBDB‐T:ITIC blends exhibits a higher power conversion efficiency of 10.03% and better stability than the optimal spin‐coated device with 1% DIO, because blade‐coating can induce a higher degree of molecular packing and partially replace the role of DIO, showing excellent prospects.